The Effect of Free Shipping, Religiosity, Hedonic Conformity and Promotion on Consumptive Behaviour in Generation Z in Banda Aceh - Nisya, Alivia; Halim, Hendra; Fakhrurrazi, Fakhrurrazi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of free shipping, religiousness, hedonic conformity and promotion on the consumption behavior of Gen-Z through simple random sampling technique that was done by questioners. The analysis used was double linear regression and was processed by Stata 17 software. The result of this research has shown that partially, some variables like free shipping and hedonic conformity are significantly influential toward the consumptive behavior. However, religiosity and promotion is not influential toward the consumptive behavior. Afterwards, simultaneously, some variables like free shipping, religiosity, hedonic conformity, and promotion are significantly influential toward the consumptive behaviors of the gen-z in Banda Aceh.